Effectiveness and Safety of Nebulized Colistin in Ventilator Associated Pneumonia - Mithun Kumar Mondal; Dutta, Sanghita (Bangladesh Critical Care Journal, 2025)
Background: Colistin is one of the few remaining effective antimicrobial agents against multidrug-resistant (MDR) and extensively drug-resistant (XDR) Gram-negative bacteria, and is currently regarded as one of the last therapeutic options. After giving aerosol delivery, colistin concentrations were significantly higher in the pulmonary epithelial lining fluid compared to plasma. This study investigates the effectiveness and safety of nebulized colistin as monotherapy (without concomitant IV administration of colistin) in the treatment of ventilator-associated pneumonia. Objective: Evaluation of the effectiveness and safety of nebulized colistin in ventilator-associated pneumonia. Methods: This prospective randomized clinical trial was conducted in the ICU of the Department of Anaesthesia, Analgesia, Palliative & Intensive Care Medicine, Dhaka Medical College Hospital. The study included patients on mechanical ventilation with ventilator-associated pneumonia sensitive to colistin organisms (Acinetobacter, Pseudomonas, Klebsiella) without prior renal impairment. Then, the patients were divided into two equal groups by computer-generated randomization by a research randomizer. Group A received intravenous colistin, and group B received nebulized colistin as a monotherapy. The analysis was carried out using descriptive and inferential statistics with the help of SPSS. Result: This prospective randomized clinical trial was conducted to see the effectiveness and safety of nebulized colistin compared to intravenous colistin. The clinical cure rate was higher in group B than in group A (65.7% in nebulized group B, 51.5% in intravenous group A), although it was not statistically significant (p=0.743). The microbiological eradication rate was also higher in nebulization group B (94.3%) compared to intravenous group A (85.7%), although it was not statistically significant (p=0.075). Nephrotoxicity is the major adverse event at 25.7% among intravenous group A compared to 5.7% in nebulized group B (p=0.001). Colistin nebulization therapy is usually well tolerated, with only a few side effects being reported. These include coughing, bronchospasm, and throat irritation, which are frequently brought on by the osmolality and preservatives in solutions. We found bronchospasm in nebulized colistin in 1 patient (1.96%). An almost equal proportion of mortality was present in both groups: 28.5% in intravenous group A and 25.7% in nebulization group B (p=0.453). Mean duration of mechanical ventilation in intravenous group A and nebulized group B were 8.19 ± 5.59 and 7.96±3.63 days, respectively (p=0.802). The mean ICU duration of the patients in intravenous group A and nebulized group B were 10.08±6.44 and 9.45±3.76 days, respectively (p=0.55). The mean CPIS (Clinical Pulmonary Infection Score) score reduction of the patients exposed to nebulized and intravenous colistin were 3.8±1.04 and 4 ± 1.17, respectively, which is not statistically significant (p= 0.372). The mean TLC (Total Leukocyte Count) normalization duration of patients in intravenous group A and nebulized group B were 7.43±2.836 and 6.51±2.87 days, respectively (p=0.14). Conclusion: Both nebulized and intravenous colistin are equally effective for treating colistin-sensitive ventilator-associated pneumonia, though intravenous colistin is more nephrotoxic. Bangladesh Crit Care J March 2025; 13 (1): 11-17